Factors determining the implementation of the cultural policy of Iran Tobacco Company: A model with an environmental responsibility approach - Hossein Kharabi; Hamdollah Manzari Tavakoli; Sanjar Salajegheh; Mohammad Jalal Kamali (Shahid Beheshti University of Medical Sciences, 2022)
Background: This study aims to investigate the cultural policies of the tobacco company in the framework of social responsibility theory. Method: This study was a cross-sectional study. The statistical population included the managers of the tobacco company (335 people). The research sample size was determined to be 275 people based on Cochran's formula and by using cluster sampling. Data were collected through a researcher-made questionnaire consisting of 32 questions. The content validity of the questionnaire was confirmed by 22 experts. The Cronbach's alpha coefficient of the variables was obtained higher than 0.7. Data were analyzed by confirmatory factor analysis and path analysis in AMOS software. Results: The results of the path coefficient between the factors related to the implementation of cultural policies and environmental responsibility were close to 0.80, and the path coefficient between environmental responsibility and cultural policies was equal to 0.18 and less than 0.3, indicating the model weakness.  Most of the factor loads belonged to the indicators of environmental advertising, contextualization, warning against tobacco consumption, information, monitoring system, legal policies, policy implementation, management style, high-quality product and cultural implications. Conclusion: It seems necessary to have a social and environmental responsibility of the tobacco company with the dimensions of "providing a quality product", "following the policies", "providing cultural messages" and "warning against tobacco consumption" as components of the policy the cultural activities of the tobacco company are considered by policymakers for implementation in three indicators: "information-information", "environmental advertising" and "cultural background".